Community health workers and promotoras' perspectives of a research best practice course: A focus group study. Issue 1 (26th September 2022) - Varma, Deepthi S.; Samuels, Elias; Piatt, Gretchen; Watkins, Daphne C.; Spiroff, Meghan; Cottler, Linda B.; Gaxiola, Sergio Aguilar; Murphy, Susan L.
Abstract: Introduction: Community Health Workers and Promotoras (CHW/Ps) are valued for their role in helping to engage community members in research. CHW/Ps have traditionally received variable training in research fundamentals, including importance and promotion of research rigor to establish consistency in the methods used over time. Research best practices training exists for research professionals, but no standard training is provided as part of the CHW/P job role. To develop this CHW/P research best practices training, our team engaged English- and Spanish-speaking CHW/Ps to watch an early version of an online module and to examine perceptions of the relevance of such a training and optimal delivery methods. Methods: Six virtual focus group discussions were conducted (three in English and three in Spanish) across different US geographic regions with currently employed CHW/Ps. Results: Forty CHW/Ps participated (95% female, mean age 44 years, 58% identifying as Hispanic/Latino). Four themes emerged: relevance of training, benefits of providing a certificate of completion, flexible training delivery modalities, and peer-led training. Discussion: With participation from representatives of the intended learner group of CHW/Ps, our team found that CHW/Ps valued learning about research best practices. They perceived culturally- and linguistically appropriate health research training to be highly relevant to their role, particularly for communicating key information to community members about their participation in health research. Additionally, participants provided input on effective dissemination of the training including the benefit of having proof of course completion, involvement of peer trainers, and value of providing the option to participate in online training.